Ethyne Functionalized Meso-Phenothiazinyl-Phenyl-Porphyrins: Synthesis and Optical Properties of Free Base Versus Protonated Species - Molnar, Eva (Molecules, 2020)
Synthesis, structural characterization and photophysical properties for a series of new trans-A(2)B(2)- and A(3)B-type ethynyl functionalized meso-phenothiazinyl-phenyl porphyrin derivatives are described. The new compounds displayed the characteristic porphyrin absorption spectra slightly modified by weak auxochromic effects of the substituents and fluorescence emission in the range of 651–659 nm with 11–25% quantum yields. The changes recorded in the UV-vis absorption spectra in the presence of trifluoroacetic acid (TFA) are consistent with the protonation of the two internal nitrogen atoms of the free-base porphyrin (19 nm bathochromic shift of the strong Soret band and one long wave absorption maxima situated in the range of 665–695 nm). Protonation of the phenothiazine substituents required increased amounts of TFA and produced a distinct hypsochromic shift of the long wave absorption maxima. The density functional theory (DFT) calculations of a porphyrin dication pointed out a saddle-distorted porphyrin ring as the ground-state geometry.